Identifying Traumatic Experiences and Their Effects on Grade 8 Students at Community Schools - Maharjan, Chhori Laxmi; Shrestha, Shristi (NPRC Journal of Multidisciplinary Research, 2025)
Background Trauma is any event that causes a person to experience intense negative and disruptive feelings, ultimately affecting the person's functioning in various areas of life. Children and adolescents with trauma are susceptible to develop Post-Traumatic Stress Disorder (PTSD) and other mental disorders. This study aimed to identify the traumatic experiences of the Grade 8 students in community schools; examine the types of Post-Traumatic Stress Symptoms (PTSS) and their severity in those students.Methods The study sample (n=166) of Grade 8 students of 3 community schools were purposively selected. The data was collected using Child and Adolescents Trauma Screen (CATS) questionnaire.Results  The 3 most common trauma types are: witnessing and experiencing physical aggression and serious natural disaster. The mean number of traumatic events is 3.84. PTSS is seen in 50.6% of the respondents. The severity is higher in females (54.1%) than in males (45.6%) and in younger adolescents (52.0%) compared to older ones (50.0%). The number of traumatic events experienced and severity of PTSS is significantly correlated. Majority of respondents reported having arousal and reactivity symptoms compared to other types of post-traumatic symptoms.Conclusion Nepali adolescents experience in average 4 traumatic events and their serious after effects. More studies on wider population are needed to examine the influence of various factors including the impact of onset and duration of trauma exposure on the severity of PTSD.Novelty This study can provide insight into the prevalence of trauma; its effects on the adolescents and highlight the importance of students' access to mental health services. In addition, this study can act as a baseline to promote trauma-informed practices in schools.